Volume and Price Patterns Around a Stock's 52-Week Highs and Lows: Theory and Evidence - Huddart, Steven; Lang, Mark; Yetman, Michelle H. (Management Science, 2009)
We provide large sample evidence that past price extremes influence investors' trading decisions. Volume is strikingly higher, in both economic and statistical terms, when the stock price crosses either the upper or lower limit of its past trading range. This increase in volume is more pronounced the longer the time since the stock price last achieved the price extreme, the smaller the firm, the higher the individual investor interest in the stock, and the greater the ambiguity regarding valuation. These results are robust across model specifications and controls for past returns and news arrival. Volume spikes when price crosses either the upper or lower limit of the past trading range, then gradually subsides. After either event, returns are reliably positive and, among small investors, trades classified as buyer-initiated are elevated. Overall, results are more consistent with bounded rationality than with other candidate explanations.